Open systems and closed networks: policy networks and the emergence of open systems in local government. - Pratchett, Lawrence (Public Administration)
Part of a special section on public administration in the information age. To understand the development of specific information and communications technology (ICT) strategies in local government, the broader issues beyond the level of individual local authorities must be considered. Therefore, a framework that provides analysis of ICT policies across a range of perspectives has considerable value. Such a framework highlights the complicated arrangement of policy networks reflecting broad socioeconomic changes and creates the environment within which interactions between individual organizations happen. An application of this framework to a case study of an open systems strategy demonstrates that technical discourse predominates over political discourse in determining ICT policies. The open systems policies emerging from the local government ICT network support the belief that ICTs are mainly a technological issue for discussion and resolution at the technical, rather than political levels of the organization.